Europe in 1777: from humanitarian critique of the existing law to creating new criminal codes - Salmonowicz, Stanisław (Studia Iuridica Toruniensia, 2017)
In the year 1777 in Europe (Switzerland and France) a few important public competitions on projects of a reform of the criminal law and criminal procedure, were conducted. The following years brought a bunch of significant works on codifications in this area. The paper presents state of the humanitarian literature circa 1777, as well as course of the competitions and authors of the projects. It emphasizes the thesis – based on the author’s own research and the newest achievements of science – that, after a period of critique of the existing criminal law, a new era of searching legislative solutions, appeared. During this era, a leading role was played by professional lawyers. This final stage of the humanitarian literature remained important even after the beginning of The Great French Revolution. The author is on the opinion, that now is an appropriate moment, to prepare a comprehensive history of a whole humanitarian reform movement. This work should not be limited only to mainstream of the humanitarian doctrine, strong in Italy, France and Germany, but it have to also include countries as Spain, Great Britain and Polish-Lithuanian Commonwealth.